(untitled) (Journal of Informatics and Mathematical Sciences, 2016)
This paper explores the following problem: Let \(A=(A,+,·)\) and \(E=(E,+,·)\) be duo binary systems. Let \(S=(S,+,·)\) be a subsystem of \(A\). Under what conditions can a homomorphism \(p:S→ E\) be extended to a homomorphism \(P:A→ E\) and how?